Cryptocurrency, Tax Imposition and Sharia Finance In Indonesia: A Systematic Literature Review - Ayu, Shilfa; Nurlaela Wati, Lela (Green Publisher Indonesia, 2022)
The purpose of this paper is to review the findings of a review of the academic literature on Islamic financial technology that has been carried out in the field of Islamic financial technology. The aspects studied in Islamic Finance Fintech with cryptocurrency regulations, compliance and tax policy laws and finally identify other influences such as opportunities and Islamic financial technology that Islamic financial institutions can learn from global fintechs around the world. This study collected 150 journals. Based on the inclusion and exclusion criteria, 79 research papers and publications were used in this systematic literature review. This paper offers a thorough analysis of the study. This study classifies Islamic Financial Technology with regulation/compliance in Islamic law and taxation. Throughout our review, we also found barriers to cryptocurrencies in Islamic law and found several countries have tax policies for cryptocurrencies. This study will greatly advance the understanding of Islamic FinTech among academics, companies, regulators, investors, and other FinTech users. The results of this study are expected to be useful in understanding Fintech (cryptocurrency-based technology) from the point of view of sharia and taxation rules in Indonesia